1995
DOI: 10.1177/014572179502100108
|View full text |Cite
|
Sign up to set email alerts
|

Foot Care Assessment in Patients with Diabetes: A Screening Algorithm for Patient Education and Referral

Abstract: The foot care behaviors of patients with diabetes were assessed by medical history, and their feet were examined for peripheral neuropathy, peripheral vascular disease, foot ulcers, and deformities. The sample consisted of 136 patients (14 with insulin-dependent diabetes and 122 with non-insulin-dependent diabetes). Mean age was 61 years and mean duration of diabetes was 13 years. Peripheral vascular disease was found in 25% of the patients, peripheral neuropathy in 33%, and 13% had both peripheral vascular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Most of them incorporated neuropathy, bony foot deformity, history of ulceration or amputation, or various combinations of these (10,(23)(24)(25)(26)(27)(28)(29). Three of them also included PVD (10,28,29). Although most early classification systems were solely based on expert clinicians' experiences, three of these systems were validated with patient data (10,26,29).…”
Section: Results -Ofmentioning
confidence: 99%
“…Most of them incorporated neuropathy, bony foot deformity, history of ulceration or amputation, or various combinations of these (10,(23)(24)(25)(26)(27)(28)(29). Three of them also included PVD (10,28,29). Although most early classification systems were solely based on expert clinicians' experiences, three of these systems were validated with patient data (10,26,29).…”
Section: Results -Ofmentioning
confidence: 99%
“…The findings of the study indicated that the routine diabetes care did not provide effective education in appropriate foot care. It is suggested that standards and guidelines for care of the diabetic foot should be developed because 50% of amputations can be prevented, according to the American Diabetes Association ( Plummer & Albert 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The Foot Care Service was developed initially to assist in the evaluation, education, and treatment of foot problems in patients with diabetes mellitus, but the program is available for all patients. A detailed history of foot care behavior and a thorough foot examination were performed by both a clinical nurse specialist and a diabetologist 10 . The history addressed aspects of routine foot care and specifically included: (1) the level of ambulation and the presence of claudication or rest pain, (2) foot care practices such as nail and callus care, foot soaks, walking barefoot, and the types of footwear, and (3) previous foot surgery, foot ulcers, or trauma.…”
Section: Methodsmentioning
confidence: 99%
“…The history addressed aspects of routine foot care and specifically included: (1) the level of ambulation and the presence of claudication or rest pain, (2) foot care practices such as nail and callus care, foot soaks, walking barefoot, and the types of footwear, and (3) previous foot surgery, foot ulcers, or trauma. Physical examination of the feet followed published guidelines for evaluation of peripheral neuropathy, peripheral vascular disease, and foot deformities 10–14 . Peripheral sensation was evaluated at 10 sites on each foot using the Semmes‐Weinstein monofilament test 15,16 .…”
Section: Methodsmentioning
confidence: 99%